Clarifying catalytic behaviors and electron transfer routes of electroactive biofilm during bioelectroconversion of CO2 to CH4. (15th February 2022) - Zhang, Zhongyi; Lu, Xueqin; Niu, Chengxin; Cai, Teng; Wang, Na; Han, Yule; Zhang, Ruiliang; Song, Yenan; Zhen, Guangyin
Graphical abstract: Highlights: CH4 generation reached 298.0 mL/L/d at −1.0 V vs. Ag/AgCl with η CE of 75.8%. Moderate EPS played a curial role in aggregation and stability of biofilm. hdrA, ehaA, and ehbC were putative genes for direct extracellular electron transfer. Potential extracellular electron transfer pathway for CH4 formation was proposed. Abstract: Bioeletromethanogenesis, as a cutting-edge option to capture CO2 and produce multi-carbon biofuels, has received extensive attraction. However, how electroactive biofilm (EAB) as the biocatalyst drives CO2 electromethanogenesis is still not well recognized. In this study, a two-chamber bioelectrochemical cell equipped with a hybrid skirt-shaped cathode was constructed and the electrocatalytic performance of EAB and the electron shuttling mechanisms involved in extracellular electron transfer (EET) were systematically studied. The EAB colonizing on biocathode showed an excellent cathodic electrocatalytic activity and the minimum charge transfer resistance. The CH4 production rate of 298.0 ± 46.7 mL/L/d was obtained at the cathodic potential of −1.0 V vs. Ag/AgCl with the highest Coulombic efficiency of 75.8 ± 9.9%. The gel-like extracellular polymeric substances, secreted by EAB, facilitated the adhesion/aggregation of microbes and EAB development. Further analysis suggested that CO2 electromethanogenesis exhibited a positive association with Methanobacterium (54.4%) in EAB. Moreover, metagenome analysis confirmed the presence of direct EET-related genes (i.e., hdrA, ehaA, and ehbC ), which accelerated the formation of corresponding functional protein complexes (particularly heterodisulfide reductase A, HdrA) and electron exchange. The mechanism for electron shuttling process in catalyzing CO2 electromethanogenesis was further proposed. This study provides a new insight into direct extracellular electron transfer (DEET) mechanisms of CO2 electromethanogenesis, and is useful for promoting EAB electrocatalytic activities and CO2 emission reduction and reuse.